EJECTA FORMATION AND CRATER DEVELOPMENT OF THE MJøLNIR IMPACT - Shuvalov V.; Dypvik H. (My University, 2004)
Crater-ejecta correlation is an important element in the analysis of crater formation and its influence on the geological evolution. In this study, both the ejecta distribution and the internal crater development of the Jurassic/Cretaceous Mjolnir crater (40 km in diameter; located in the Barents Sea) are investigated through numerical simulations. The simulations show a highly asymmetrical ejecta distribution, and underscore the importance of a layer of surface water in ejecta distribution. As expected, the ejecta asymmetry increases as the angle of impact decreases. The simulation also displays an uneven aerial distribution of ejecta. The generation of the central high is a crucial part of crater formation. In this study, peak generation is shown to have a skewed development, from approximately 50-90 sec after impact, when the peak reaches its maximum height of 1-1.5 km. During this stage, the peak crest is moved about 5 km from an uprange to a downrange position, ending with a final central position which has a symmetrical appearance that contrasts with its asymmetrical development.